Applicability of protein estimation methods for assaying glycomacropeptide. (15th September 2017) - Narwal, Vikrant; Sharma, Neelima; Sharma, Rajan; Rajput, Yudhishthir S; Mann, Bimlesh
Abstract : Glycomacropeptide (GMP) is a nutraceutical additive, which is released during cheese preparation. In this study, the protein content in a laboratory GMP preparation and two commercial GMP samples, which was estimated by the Bradford, biuret, Lowry and bicinchoninic acid (BCA) assays, were compared using the Kjeldahl method. There were apparent differences in the values of estimated proteins using the different methods. An absence of dose response in the Bradford method and a low dose response using the Lowry method indicated the unsuitability of both these methods. Absorbance in the biuret and BCA methods linearly increased with increasing GMP content. The BCA method was the most sensitive of these methods.